![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a)\(\frac{3^{10}.\left(-5\right)^{21}}{\left(-5\right)^{20}.3^{12}}=\frac{-5}{9}\)
b)\(\frac{\left(-11\right)^5.13^7}{11^5.13^8}=-\frac{1}{13}\)
c)\(\frac{2^{10}.3^{10}-2^{10}.3^9}{2^9.3^{10}}=\frac{2^{10}.3^9\left(3-1\right)}{2^9.3^{10}}=2\)
d(\(\frac{5^{11}.7^{12}+5^{11}.7^{11}}{5^{12}.7^{12}+9.5^{11}.7^{11}}=\frac{5^{11}.7^{11}\left(7+1\right)}{5^{11}.7^{11}\left(35+9\right)}=\frac{1}{6}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,-\frac{4}{7}+\left(-\frac{2}{3}+\frac{3}{7}\right)=-\frac{4}{7}-\frac{2}{3}+\frac{3}{7}=-\frac{4}{7}+\frac{3}{7}-\frac{2}{3}=-\frac{1}{7}-\frac{2}{3}=-\frac{17}{21}\)
\(b,-\frac{3}{10}\cdot\frac{5}{12}+-\frac{3}{10}\cdot\frac{7}{12}+5\cdot\frac{3}{10}=\frac{3}{10}\cdot-\frac{5}{12}+\frac{3}{10}\cdot-\frac{7}{12}+5\cdot\frac{3}{10}=\frac{3}{10}\cdot\left(-\frac{5}{12}-\frac{7}{12}+5\right)\)
\(=\frac{3}{10}\cdot4=\frac{6}{5}\)
ti ck nha
đúng đó
xin đó
#####
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{-4}{7}+\left(\frac{-2}{3}+\frac{4}{7}\right)\)
\(=\frac{-4}{7}+\frac{-2}{3}+\frac{4}{7}\)
\(=\left(\frac{-4}{7}+\frac{4}{7}\right)+\frac{-2}{3}\)
\(=0+\frac{-2}{3}=\frac{-2}{3}\)
~ Hok tốt ~
\(\frac{-3}{10}.\frac{5}{12}+\frac{-3}{10}.\frac{7}{12}+5\frac{3}{10}\)
\(=\frac{-3}{10}.\frac{5}{12}+\frac{-3}{10}.\frac{7}{12}+\frac{53}{10}\)
\(=\frac{-3}{10}.\left(\frac{5}{12}+\frac{7}{12}\right)+\frac{53}{10}\)
\(=\frac{-3}{10}.1+\frac{53}{10}\)
\(=\frac{-3}{10}+\frac{53}{10}=\frac{50}{10}=5\)
~ Hok tốt ~
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a)\frac{3^{10}.\left(-5\right)^{21}}{\left(-5\right)^{20}.3^{12}}=\frac{-5}{3^2}=\frac{-5}{9}\)
\(b)\frac{-11.13^7}{11^5.13^8}=\frac{-1}{11^4.13}\) (Bạn xem thử xem có sai đề không nhé)
\(c)\frac{2^{10}.3^{10}-2^{10}.3^9}{2^9.3^{10}}=\frac{2^{10}.3^9\left(3+1\right)}{2^9.3^{10}}=\frac{2.4}{3}=\frac{8}{3}\)
\(d)\frac{5^{11}.7^{12}+5^{11}.7^{11}}{5^{12}.7^{12}+9.5^{11}.7^{11}}=\frac{5^{11}.7^{11}\left(7+1\right)}{5^{11}.7^{11}\left(5.4+9\right)}=\frac{8}{20+9}=\frac{8}{29}\)
\(a)\frac{3^{10}\cdot\left(-5\right)^{21}}{\left(-5\right)^{20}\cdot3^{12}}=\frac{-5}{3^2}=\frac{-5}{9}\)
\(b)\frac{\left(-11\right)\cdot13^7}{11^5\cdot13^8}=\frac{-1}{11^4\cdot13}=\frac{-1}{14641\cdot13}=\frac{-1}{190333}\)
\(c)\frac{2^{10}\cdot3^{10}-2^{10}\cdot3^9}{2^9\cdot3^{10}}=\frac{2^{10}\left(3^{10}-3^9\right)}{2^9\cdot3^{10}}=\frac{2^{10}\cdot3^9\left(3-1\right)}{2^9\cdot3^{10}}=\frac{2^{10}\cdot3^9\cdot2}{2^9\cdot3^{10}}=\frac{2\cdot2}{3}=\frac{4}{3}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a)2/9-(-4/9)=6/9=2/3
b)(-1/24+0,25+1 1/12):(-1/2)2
=(-1/24+6/24+26/24):(-1/2).2
=31/24.-2.2
=-31/12.2
=-31/6
c)3/13.(-5/9)+10/13.(-5/9)+(-4/9)
=-5/9(3/13+10/13)+(-4/9)
=-5/9.1+(-4/9)
=-1